A review of design fixation: research directions and key factors. Issue 1 (3rd April 2018) - Alipour, Leyla; Faizi, Mohsen; Moradi, Asghar Mohammad; Akrami, Gholamreza
Abstract: Design fixation refers to designing under the influence of precedents with the inappropriate reuse of their features. With the aim of better understanding of design fixation and create a compendious framework, this paper reviewed 50 new empirical studies in this area. Design fixation studies are classified into (a) investigating conditions that affect design fixation occurrence, (b) proposing affordance sources, and (c) suggesting overcome instructions and methods. Results indicated that there exist eight key factors, namely designer, design problem, sources, design process, design outcome, designers' goal, distance between source and problem, and similarity between source and design outcome. Finally, a new framework was developed on the basis of the key factors and variables. By synthesizing the variables and the findings of these papers, future research directions are proposed.